A Contrastive Analysis of Interrogative Sentences in English and Indonesian - Mashlihatul Umami (IAIN Salatiga, 2015)
The aim of this paper is to investigate the forms of questions in English and Indonesian in order to identify the similarities and differences between them. CA may look at linguistic structures in a twofold way: predictability power and wash back effect (Cheng, Watanabe Curtis, 2004). The former deals with foreseeing the areas of problems the English learners may commit and the latter refers to the effect of diagnostic value of CA on improvement of teaching processes. In this case, the researcher emphasizes her study in analyzing CA based on the first perspective; this study focuses on interrogative sentences which are in the form of questions which play an important role in learning English among junior English students. This study has found the differences and similarities between Indonesian and English. Recognizing this will contribute to the accuracy of English questions made by the students.Keywords: Interrogative sentences; English; Indonesian; Contrastive analysis, accuracy